Mathematics questions in tests of admission to the Polytechnic College of Federal University of Santa Maria (2015-2020): an analysis based on two records of semiotic representation (Research, Society and Development, 2020)
This research aims to analyze Mathematics questions in selection tests for entry to High School at the Polytechnic College of the Federal University of Santa Maria (UFSM), in the period from 2015 to 2020, according to the records of semiotic representation and the principles of the qualitative approach, of bibliographic nature, following the assumptions of Content Analysis. For this, three categories of analysis are considered: Concepts/contents involved, Contextualization and Records of semiotic representation mobilized and transformations of treatment and conversion. Among the results, it is identified that the concepts of arithmetic and algebra, as well as the area of flat figures, are the most discussed; it appears that most of the questions do not contain contextualization, those that do are related, in a more expressive way, to social practices, but also to mathematics itself, history or other disciplines. In addition, there is a variety of representation records that need to be mobilized to resolve issues and that most require cognitive conversion transformations to resolve them.